A Cross-Sectional Study of the Relationship of Physical Activity with Depression and Cognitive Deficit in Older Adults - Paulo, Thais R. S.; Tribess, Sheilla; Sasaki, Jeffer Eidi; Meneguci, Joilson; Martins, Cristiane A.; Freitas, Ismael F. [UNESP]; Romo-Perez, Vicente; Virtuoso, Jair S. (Human Kinetics Publ Inc, 2016)
The aim of this study was to examine the association of physical activity with depression and cognition deficit, separately and combined, in Brazilian older adults. We analyzed data from 622 older adults. Physical activity was assessed using the International Physical Activity Questionnaire. Depressive symptoms were assessed using the Geriatric Depression Scale, while cognitive deficit was assessed using the Mini-Mental State Examination. Multinomial logistic regressions were used to assess associations of depression and cognitive deficit with sociodemographic, health, and behavioral variables. Prevalence of physical inactivity (< 150 min of moderate-to-vigorous physical activity/week), depression, and cognitive deficit were 35.7%, 37.4%, and 16.7%. Physical inactivity was associated with depression (OR: 1.83, 95% CI: 1.14-2.94) and with depression and cognitive deficit combined (OR: 4.23, 95% CI: 2.01-8.91). Physically inactive participants were also more likely to present limitations in orientation and language functions. Physical inactivity was associated with depression and also with depression and cognitive deficit combined in older adults.
Keywords: physical activity; cognitive deficit; cognitive function; depression; older adults